Peran Qawaid Fiqhiyyah Dalam Pengembangan Ekonomi Syariah - Aslamiyah Nur Hakim, El-Diena (RJABM (Research Journal of Accounting and Business Management), 2024)
ABSTRACTQawaid Fiqhiyyah is a collection of general rules of jurisprudence covering all branches of jurisprudence which serve as guidelines for determining the law on every jurisprudential issue, whether it has been designated by texts or has not had texts. Qawaid al-fiqhiyyah cannot be separated from sharia economic activities, especially in facing general economic developments such as today. In fact, these scientific disciplines are the basis for sharia economic activities so that they run according to the will of Allah SWT.  Qawaid al-Fiqhiyah plays a strengthening role in the mind, giving rise to reasons and considerations for determining the law of 'illat determining the directions of its formation, and paving the way towards the purpose of establishing the law of 'Maqashid al-Syari'ah', namely the benefit of the people, Mashalih al- Anam. In sharia economic transactions, it cannot be separated from Musyarakah, Mudharabah, Murabahah, Musawamah, Ijarah, Wakalah, Musahamah, Wadi'ah contracts and many other economic contracts and concepts in financial institutions.